Inclusion of Lotus tenuis in beef cattle systems in the Argentinian flooding pampa as an enteric methane mitigation strategy - González, Franco Alexis; Cosentino, Vanina Rosa Noemi; Loza, Cecilia; Ceron Cucchi, Maria Esperanza; Williams, Karen Evelyn; Bualo, Ricardo Alberto (Taylor and Francis, 2024)
While concerns about greenhouse gas (GHG) emissions and animal welfare persist, livestock farming offers unique ecosystem services. In Argentina, where livestock significantly contributes to GHG emissions, particularly enteric methane (CH4), urgent action is required to develop effective mitigation strategies while maintaining animal performance. This study assesses the potential of the inclusion of Lotus tenuis in natural grasslands to mitigate CH4 emissions and improve forage quality in the Salado River basin, Argentina. Twenty-four beef heifers (361 ± 19 kg LW) were assigned to two treatments with contrasting botanical composition (LOT: > 80% Lotus tenuis and NG: > 60% grasses). LOT showed better forage quality and reduced CH4 emissions (−17% gCH4/day, p < 0.01; Ym: - 7 to −30%, p < 0.05) compared to NG. However, the condensed tannin content in LOT was insufficient to conclusively attribute any impact on CH4 emissions. This study underscores the potential of promoted Lotus tenuis pastures in the Salado River basin to enhance forage quality and mitigate enteric CH4 emissions in free-ranging cattle systems, albeit additional research is necessary to fully comprehend how this practice interacts within the ecosystem and optimise its benefits